The vector projection of normalized interferogram differences and its application in phase-shift estimation. Issue 8 (27th April 2016) - Li, Teng; Hong, Daxiang
Abstract : From three interferograms, a novel algorithm for extracting phase shifts based on the vector projection of normalized difference maps is presented. In it, subtraction and vector normalization are operated successively to obtain two normalized interferogram differences without the effect of background component. Then, the phase shift can be estimated based on the analysis and calculation of the vector projection. Without any iteration and complex calculation, this algorithm can be implemented for phase-shift range approximately being well distributed from 0 to 2 π, when fringe number of interferograms is more than one. It offers a powerful tool for rapid calibration of phase shifts because of its high efficiency and easy implementation. Numerical simulations and experiments are performed to prove its validity.